2009
DOI: 10.1002/vnl.20202
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cross section design and testing conditions on the flexural properties of wood/PVC composite beams

Abstract: Highly filled wood/poly(vinyl chloride) (WPVC) composites were manufactured in five different cross sections by using an industrial-scale twin-screw extruder. The flexural properties of such composites were evaluated, with the effects of sample direction, span length, and rate of loading also being taken into account. The experimental results suggested that the cross section design of WPVC composite products had a significant effect on the flexural properties. Better flexural properties were obtained when test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 31 publications
3
24
0
Order By: Relevance
“…Most researchers have found that adding natural fibers, wood flour, wood pulp, sisal, flax, bamboo, sunhemp, pineapple, and jute into thermoplastics usually results in lower ultimate mechanical strength of the composites [14–23], although work has been done to improve the mechanical and engineering properties of such composites, including chemical surface treatments, reinforcements with glass fibers [24] and long natural fibers [25], reinforcement with nanofillers [26–28], and processing and die designs [12]. Méndez et al [14] found that the mechanical strength of PP decreased with increasing wood pulp content because of PP and wood incompatibilities.…”
Section: Introductionmentioning
confidence: 99%
“…Most researchers have found that adding natural fibers, wood flour, wood pulp, sisal, flax, bamboo, sunhemp, pineapple, and jute into thermoplastics usually results in lower ultimate mechanical strength of the composites [14–23], although work has been done to improve the mechanical and engineering properties of such composites, including chemical surface treatments, reinforcements with glass fibers [24] and long natural fibers [25], reinforcement with nanofillers [26–28], and processing and die designs [12]. Méndez et al [14] found that the mechanical strength of PP decreased with increasing wood pulp content because of PP and wood incompatibilities.…”
Section: Introductionmentioning
confidence: 99%
“…1. This die profile and the WPVC cross‐section were suggested by our previous work [18] to give relatively high mechanical properties. WPVC extrudates were solidified by passage through a cooling system and a size‐control device before collection for preparing test samples.…”
Section: Methodsmentioning
confidence: 65%
“…After that, the PVC compound was dry‐blended with the wood particles by a high‐speed mixer for 2 min before they were melt‐blended in an industrial‐scale twin‐screw extruder (KMD‐90‐36, KraussMaffei Technologies GmbH, Germany) with counter‐rotating screws. The processing conditions (processing temperature and screw rotation speed) and screw configuration were similar to those detailed in our previous work [18]. A WPVC composite sample with three hollow cores was produced and its die dimensions are given in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their strength is still limited. 4,5 Wood fiber can be used as an inexpensive filler material for recycled plastics, such as bottles and polyvinyl chloride (PVC) pipe. Many researchers have focused on the characterization of various types of WPCs.…”
Section: Introductionmentioning
confidence: 99%